INFLUENCE OF HERBAL EXTRACTS ON METABOLIC DISTURBANCES IN DIABETES MELLITUS AND INSULIN RESISTANCE MODEL - T. V. Yakimova; O. N. Nasanova; A. I. Vengerovsky (Бюллетень сибирской медицины, 2015)
The aim of this research was to assess the influence on metabolic processes of herbal extracts, used in diets with different fat content, in diabetes mellitus and insulin resistance model.Material and methods. The experiments were performing on 90 noninbred male albino rats. Diabetes mellitus was modeling with twice-repeated intraperitoneal streptozotocine (30 mg/kg) injections. For the insulin resistance formation animals were fad meal with 30% fat content. Against the background rats were administering into the stomach nettle leafs (Urtica dioica L., 100 mg/kg), burdock roots (Arctium lappa L., 25 mg/kg) extracts or intraperitoneal insulin preparation Actrapide HM Penfill (3 mg/kg) daily during 10 days. During period of agents introduction one-half of animals continued to receive food with high fat content, the other half received diet with 8% fat content. The third rats group received only food with low fat content without extracts or insulin administration. In blood was measured the glucose, glycosylated hemoglobin, creatinine, urea, uric acid content, in liver homogenates – glycogen, protein content, aminotransferases and glucose-6phosphatase activity, in muscle homogenates – glycogen and protein content.Results. After streptozotocine injections and diet with 30% fat content the blood glucose level became by 4.0–5.3 fold more than level of intact animals, increased the hemoglobin glycosylation, also creatinine, urea, uric acid blood content, in liver and muscle homogenates raised glycogen content, decreased protein quantity, in liver homogenates increased aminotranferases and glucose-6-phosphatase activity. In animals only feeding with 8% fat diminished hyperglycemia, creatinine blood retention, the liver glycogen content and recovered its protein resources. The nettle or burdock extracts administrating to animals that continued to receive high fat meal decreased the blood glucose, glycosylated hemoglobin and creatinine content, the liver glucose-6-phosphatase activity, increased the muscle protein content, the nettle extract also prevented from hyperuricemia and liver protein deficiency, the burdock extract caused the liver glycogen accumulation. In animals feeding with low fat meal the nettle extract caused hyperglycemia parameters regression and changed in the direction of the norm the liver and muscle glycogen content, the burdock extract decreased only hemoglobin glycosylation, both herbal extracts decreased the blood creatinine level and increased the muscle protein level. Independently of diet the nettle extract increased the insulin sensitivity after 60 and 120 min after insulin injection, the burdock extract – after 120 min.Conclusion. The nettle and burdock extracts have in diabetes mellitus and insulin resistance model hypoglycemic action, prevent from hemoglobin glycosylation, improve creatinine excretion, recover the muscle sensitivity to insulin effect.